Legal analysis of change of gender of TNI soldiers from the perspective of Military Administrative Law - Irfan Rifa’i (Goodwood Publishing, 2024)
Purpose: Gender reassignment has become a complex and sensitive issue in various aspects of life, including in the military context. This study is motivated by the case of Sergeant First Class Aprilio Perkasa Manganang, who underwent gender reassignment based on Law Number 23 of 2006 concerning Population Administration without any specific regulation in military law. Research methodology: This study uses a normative juridical method with a statutory regulatory approach and conceptual analysis. Results: The results of the study indicate that currently there are no regulations that specifically regulate gender reassignment for TNI soldiers. However, the TNI institution strictly prohibits gender reassignment for its soldiers, considering the importance of stability, discipline, and order in the military environment. This prohibition is based on the principle that TNI soldiers must live their lives in accordance with their initial identities that have been determined in the recruitment process. Further analysis shows that although Law Number 23 of 2006 concerning Population Administration accommodates gender reassignment, this regulation cannot be applied directly in the military context. Therefore, special regulations are needed that clearly regulate the prohibition of gender reassignment for TNI soldiers as well as administrative procedures that support this policy. Conclusions: This study concludes that regulations prohibiting gender reassignment for TNI soldiers need to be strengthened in military administrative law to ensure legal certainty and discipline in military institutions. In addition, there needs to be a clear monitoring and implementation mechanism to prevent abuse and maintain the integrity and professionalism of TNI soldiers.